Assessing Small – holder Participation in Value Chains: The Case of Vegetables in Honduras and El Salvador - Lundy, Mark M.; Banegar, Roberto; Centeño, Lourdes; Rodríguez, Iván; Alfaro, Manuel; Hernández, Santos; Cruz, José Ángel (Alianzas de Aprendizaje, 2006)
The document addresses the theme of value chains, and in this sense suggests strategies so that the development of these chains is focused on collaborative actions among the actors. The text also shows that there are some key areas of intervention such as the development of more organizational models for small producers, testing of various methods of chain management and coordination, and the institutionalization of public policies based on a more complete monitoring of The social, environmental and economic impacts that affect the food sector in Central America.